PROFITABILITY AS A LIQUIDITY AND RISK FUNCTION BASING ON THE NEW CONNECT MARKET IN POLAND - Bolek, Monika (European Scientific Journal, ESJ, 2013)
In this article the author examines the relationship between profitability and liquidity and risk in emerging companies listed on the New Connect market in Warsaw. This article aims to analyze the five main indicators of profitability expounded by the liquidity ratios that represent different approaches to it. In addition, risk indicators were taken into account in order to deepen the analysis. You may find that different measures profitability are associated with different indicators of liquidity.